Mass dependence of ultracold three-body collision rates - D’Incao, J. P.; Esry, B. D. (My University, 2006)
We show that many aspects of ultracold three-body collisions can be controlled by choosing the mass ratio between the collision partners. In the ultracold regime, the scattering length dependence of the three-body rates can be substantially modified from the equal mass results. We demonstrate that the only nontrivial mass dependence is due solely to Efimov physics. We have determined the mass dependence of the three-body collision rates for all heteronuclear combinations relevant for two-component atomic gases with resonant s-wave interspecies interactions, i.e., three-body systems with two identical bosons or two identical fermions.